how do I solve the equation (y+6) divided by 3- (y-3) divided by2=2

2 answers

[(y+6)/3] - [(y-3)/2] = 2

Is it the prob?
If so, it will be

(y+6)2 - (y-3)3 = 2*3*2
2y+12 - (3y-9) =12
2y +12 -3y +9 =12
-y = -9
y = 9
Similar Questions
    1. answers icon 2 answers
  1. how do you know if one is a factor of another without dividing.a) 4320 can be divided be divided by 2,5,10 evenly. How? b)can
    1. answers icon 2 answers
  2. 1.62 divided by 0.816.2 divided by 8 0.0162 divided by 0.008 0.162 divided by 0.08 There are actually two different ways to
    1. answers icon 8 answers
    1. answers icon 5 answers
more similar questions